Influence of ecological protection on the corporate image of oil and gas firms in Nigeria - Deborah Bolanle Motilewa; Ayodotun Stephen Ibidunni; Rowland Worlu; Chinonye Love Moses; James Obi; Joy Dirisu (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Oil and gas firms in Nigeria are generally perceived to be weak in their environmental and ecological initiatives towards their host communities. Yet there has been a dearth of empirical emphasis from research that shows evidences about the role of ecological protection on the corporate image of oil and gas firms. Therefore, this study focused on examining the influence of a commitment to ecological protection on the corporate image of oil and gas firms in Nigeria. The study adopted the mixed methods approach where quantitative and qualitative methods (survey and interview) were used. For the quantitative research, copies of structured questionnaire were distributed to 350 employees of the selected firms, while 30 respondents from other stakeholder groups were interviewed for the qualitative research. Based on the results of the regression and thematic analyses, findings show that the firms' commitment to ecological protection through their policy to avoid the use of materials from the illegal exploitation of natural resources, commitment to waste minimisation and recycling and pollution leads to increased investors' confidence, strengthened relationship with the government, host community and reduced pressure from third parties. Therefore, it is recommended that oil and gas firms intensify efforts in activities that ensure ecological protection of host communities and thus build stakeholders confidence in the firms' corporate image.
Keywords: M1; 650; ecological protection; corporate social responsibility; corporate image; oil and gas firms; Nigeria